Reorientasi Kebijakan Non-Blok Swedia ke NATO: Analisis Strategi Balancing Threat Terhadap Ancaman Eksistensial Rusia - Semeion El Sozo; Deasy Silvya Sari (Department of International Relations, Brawijaya University, 2026)
This study examines Sweden’s historic shift from military non-alignment to joining NATO as its 32nd member. Based on primary data from an interview with the Swedish Ambassador to Indonesia, H.E. Daniel Blockert, the research identifies Russia's full-scale invasion of Ukraine in February 2022 as the primary catalyst for this paradigm shift. The findings suggest that Sweden’s motivations were driven by an existential security threat and the strategic necessity of synchronizing defense policies with neighboring Finland. The integration offers fundamental advantages, including collective defense guarantees under Article 5, enhanced control over the Baltic Sea region which is now effectively a